Réponses

2013-08-29T16:07:53+02:00
   1)   E(x)  =  (3x − 1) ( 4x + 1) − (3x − 1) (4x − 3)
                  =  (12x² + 3x − 4x − 1) − (12x² − 9x − 4x + 3)
                  =  12x²  + 3x − 4x − 1 − 12x² + 9x + 4x − 3
                  =  12x − 4


   2)   E(x)  =  (3x − 1) ( 4x + 1) − (3x − 1) (4x − 3)
                  =  (3x − 1) [ (4x + 1) − (4x − 3) ]
                  =  (3x − 1) (4x + 1 − 4x + 3)
                  =  4(3x − 1)


   3)   E(x)  =  4(3x − 1)
                  =  12x − 4           qui est bien la même expression qu'en 1).


    4)   E(x)  =  12x − 4

          E(0)  =  12(0) − 4
                   =  0 − 4
                   =  −4

          E(−2)  =  12(−2) − 4
                     =  −24 − 4
                     =  −28

          E(0)  =  12(−4/3) − 4
                   =  4(−4) − 4
                   =  −16 − 4
                   =  −20